The Potential of Jonggol Garden in Cibodas Village in the Prospect of Developing Ecotourism - Meliantari, Dian; Apriani, Ari; Tarmizi, Achmad (KnE Social Sciences, 2023)
The Covid-19 pandemic has devastated the Indonesian economy, including the tourism industry. After the pandemic, tourism began to reopen. This study aims to find out the potentiality and obstacles of Jonggol Garden after the pandemic. The method used is the quantitative purposive sampling and incidental sampling through the provision of questionnaires, interviews, and secondary data from literature materials. Analyze with SWOT to see the potential and obstacles of Jonggol Garden. Followed by univariate and bivariate analysis for each of the observed. Keywords: post-pandemic, ecotourism, Jonggol tourism, Jonggol Garden, creative economy